Cost and Benefits from Infrastructure Competition : Estimating Welfare Effects from Broadband Access Competition - Felix Höffler (Max Planck Institute for Research on Collective Goods, 2005)
Competition between parallel infrastructures incorporates opposing welfare effects. The gain from reduced deadweight loss might be out- weighed by the inefficient duplication of an existing infrastructure. Using data from broadband internet access for Western Europe 2000-2004, this paper investigates which effect prevails empirically. Infrastructure competition between DSL and cable TV had a significant and positive impact on the broadband penetration. Comparing the additional social surplus attributable to cable competition with the cable investments, we conclude that infrastructure competition has not been welfare enhancing. A theoretical model is provided, formalizing why the effect of competition on penetration might be limited.
Keywords: L96; L12; L51; K23; L86; 330; Infrastructure Competition; Service Competition; Broadband; Internet; Cable TV; DSL; Breitbandkommunikation; Netzzugang; Wettbewerb; Kosten-Nutzen-Analyse; Wohlfahrtseffekt; Theorie